The need for diversity in teaching law / Sheela Jayabalan - Jayabalan, Sheela (Penerbit UiTM (UiTM Press), 2018)
Teaching law is normally depicted with students seated in a large lecture theatre with the professor in law who lectures in the traditional lecture method feeding students with the content of law. This content is faithfully taken down by students as notes while trying to make sense of the professor's lectures. This was the norm of teaching law some 20 years back during the author's student time and still is the practice because the lecture method is the most efficient means to cover the vast subject content of law. Furthermore, it is opined that it is easier to expound one's views than to ask penetrating questions which rarely provoke the activity of original thinking. As such, law students are inundated with substantive and procedural law. Little thought is given to the learning process. The corpus of learning the law becomes less significant. Emphasis is on teaching the law. The traditional teaching norm of lecture method is so innate that the traditional method of teaching law is perpetuated, dragging the students into a dry and boring journey of studying law. Even though the study of law is daunted as a serious one, but equal significance should be given to provoke the cognitive thinking of the students. Law students should be taught to think like a lawyer. Additionally, some form of creativity can be an added value in teaching law which makes learning law more vibrant. This article laments that the traditional pedagogy of teaching law merely imparts knowledge, whereas law students should be taught to learn the law, stimulate critical thinking and ignite their cognitive skills.